A case of neonatal Jeune syndrome expanding the phenotype. Issue 4 (2nd June 2014) - Drera, Bruno; Ferrari, Daniela; Cavalli, Pietro; Poggiani, Carlo
Key Clinical Message We report the case of a premature, very low birth weight, newborn with stigmata of Jeune syndrome, a rare skeletal dysplasia, and marked renal involvement (i.e. remarkable prenatal oligohydramnios, histologic nephronophthisis‐like pattern, macroscopic renal cysts, and renal failure), expanding the phenotype consistent with the continuum of syndromic ciliopathies.